Cimetidine-induced vascular cell apoptosis impairs testicular microvasculature in adult rats - Beltrame, Flávia L.; Yamauti, Caroline T. [UNESP]; Caneguim, Breno H.; Cerri, Paulo Sérgio [UNESP]; Miraglia, Sandra M.; Cerri, Estela Sasso [UNESP] (My University, 2012)
Cimetidine, an H2 receptor antagonist used for treatment of gastric ulcers, exerts antiandrogenic and antiangiogenic effects. In the testes cimetidine impairs spermatogenesis, Sertoli cells and peritubular tissue, inducing apoptosis in the myoid cells. Regarding the importance of histamine and androgens for vascular maintenance, the effect of cimetidine on the structural integrity of the testicular vasculature was evaluated. Adult male rats received cimetidine (CMTG) and saline (CG) for 50 days. The testes were fixed in buffered 4% formaldehyde and embedded in historesin and paraffin. In the PAS-stained sections, the microvascular density (MVD) and the vascular luminal area (VLA) were obtained. TUNEL method was performed for detection of cell death. Testicular fragments embedded in Araldite were analyzed under transmission electron microscopy. A significant decrease in the MVD and VLA and a high number of collapsed blood vessel profiles were observed in CMTG. Endothelial cells and vascular muscle cells were TUNEL-positive and showed ultrastructural features of apoptosis. These results indicate that cimetidine induces apoptosis in vascular cells, leading to testicular vascular atrophy. A possible antagonist effect of cimetidine on the H2 receptors and/or androgen receptors in the vascular cells may be responsible for the impairment of the testicular microvasculature.
Keywords: Cell death; H2 receptor antagonist; Microvascular density; Smooth muscle cell; Vascular atrophy; antiulcer agent; cimetidine; histamine H2 receptor antagonist; animal; apoptosis; atrophy; drug effect; male; microvasculature; pathology; rat; Sprague Dawley rat; testis; transmission electron microscopy; vascularization; Animals; Anti-Ulcer Agents; Apoptosis; Atrophy; Cimetidine; Histamine H2 Antagonists; Male; Microscopy, Electron, Transmission; Microvessels; Rats; Rats, Sprague-Dawley; Testis